Pengembangan Budidaya Ikan Lele di Sendang Secekel - Via Angelina Firdaus; Edy Raharja (Faculty of Economics and Business Diponegoro University, 2026)
The high level of catfish consumption in Indonesian, particularly in the City of Semarang, indicates significant opportunities for the development of freshwater aquaculture businesses. Sendang Secekel is a catfish farming enterprise that operates two business models, namely hatchery and grow-out cultivation. Differences in technical characteristics, cost structures, risk levels, and revenue contributions between these two activities require appropriate business planning. The main problem in this study is the absence of a structured business plan to determine the direction of business development. This study aims to analyze the business environment of catfish farming at Sendang Secekel, assess the feasibility of hatchery and grow-out activities, and develop a business plan. This study uses a descriptive qualitative method supported by a quantitative approach. Data were obtained through observation of farming activities, internal financial data, interviews with farming members and consumers, and literature studies. The analysis was conducted using SWOT analysis supported by IFAS and EFAS matrices, followed by a feasibility analysis covering market, operational, human resource, and financial aspects through the calculation of profit and loss projections, cash flow, Break Even Point, Net Present Value, Internal Rate of Return, and Payback Period. The results show that Sendang Secekel has main strengths in the availability of natural water resources and high market demand for consumption-size catfish. Grow-out farming contributes the largest share of revenue and is considered feasible as the main focus of business development, while hatchery activities serve as a supporting business to maintain supply sustainability.